Conceptual Analysis of Circular Economy, Perspectives, And Applications: A Critical Review. - Castillo Villares, José Luis (2023)
This article presents an overview of the circular economy, exploring its foundations, practices and perspectives. Through a literature review and use of QDA Miner software, information from 10 selected articles was analyzed. The results revealed the importance of reuse, reduction and recirculation of materials, as well as the need for systemic changes and multi-stakeholder collaboration. Although the implementation of the circular economy faces challenges, its potential to address the negative impacts of linear production and promote economic-environmental sustainability is recognized. The circular economy offers a strategy for a more sustainable and resilient future.